The rodent malaria lactate dehydrogenase assay provides a high throughput solution for in vivo vaccine studies. Issue 4 (August 2015) - Otsuki, Hitoshi; Yokouchi, Yuki; Iyoku, Natsumi; Tachibana, Mayumi; Tsuboi, Takafumi; Torii, Motomi
Abstract Rodent malaria is a useful model for evaluating the efficacy of malaria vaccine candidates; however, labor-intensive microscopic parasite counting hampers the use of an in vivo parasite challenge in high-throughput screening. The measurement of malaria parasite lactate dehydrogenase (pLDH) activity, which is commonly used in the in vitro growth inhibition assay of Plasmodium falciparum, may be the cheapest and simplest alternative to microscopic parasite counting. However, the pLDH assay has not been applied in the in vivo rodent malaria model. Here, we showed that the pLDH assay is reliable and accurately determines parasitemia in the rodent malaria model. pLDH activity measured using a chromogenic substrate reflects the parasite number in the blood; it allows fast and easy assessment using a conventional microplate reader. To validate this approach, we synthesized recombinant PyMSP1-19 protein (rPyMSP1-19) using a wheat germ cell-free protein synthesis system and immunized mice with rPyMSP1-19. The antisera showed specific reactivity on the surface of the Plasmodium yoelii merozoite and immunized mice were protected against a lethal P. yoelii 17 XL challenge. The pLDH assay quickly and easily demonstrated a significant reduction of the parasite numbers in the immunized mice. Accordingly, the pLDH assay proved to be an efficient alternative to rodent malaria parasite counting, and may therefore accelerate in vivo vaccine candidate screening.